(untitled) (Comprehensive Journal of Science, 2026)
The study aimed to analyze the impact of migrant labor on the economy and society in Libya, by examining the extent of its impact on various economic sectors and community relations The study also addressed the role of migrant labor in improving some aspects of the national economy, in addition to its impact on the Libyan labor market The societal challenges and concerns resulting from the increasing migrant labor in Libya were also examined, including issues related to unemployment among Libyans and the pressure on public services The economic and social literature was reviewed to understand the role of migrant labor in enhancing or diminishing economic and social stability in the country